Effects of straw return on C2–C5 non-methane hydrocarbon (NMHC) emissions from agricultural soils. (January 2015) - Wang, Ran; Wu, Ting; Dai, Wanhong; Liu, Hui; Zhao, Juan; Wang, Xinming; Huang, Feiyu; Wang, Zhe; Shi, Chengfei
Abstract: The effect of crop straw return on C2 –C5 non-methane hydrocarbon (NMHC) emissions from agricultural soils is investigated using a laboratory-controlled incubation of agricultural soils amended with crop straw for a period of 56 days. The average emission fluxes of total C2 –C5 NMHCs from amended agricultural soils are 304 and 173 ng kg −1 h −1 under non-flooded and flooded conditions, respectively. Alkenes are the principal emitted C2 –C5 NMHCs from amended agricultural soils, where a predominance of ethene, propene and 1-butene together shared 65% and 59% of the total C2 –C5 NMHCs under non-flooded and flooded conditions, respectively. The emissions rates of the above top three alkenes and the total C2 –C5 alkenes from amended agricultural soils under non-flooded conditions are one to four times those under flooded conditions, and these average values are 14–89 and 5–34 times those in their corresponding control treatments, respectively. These results imply that straw return contributes substantially to the emissions of light alkenes from agricultural soils, particularly under non-flooded conditions. The high correlation between microorganisms and C2 –C5 NMHC fluxes from amended agricultural soils suggest that microbes play an important role in C2 –C5 NMHC emissions from straw-amended agricultural soils. A rough estimate indicates that crop straw return could contribute insignificantly to global C2 –C5 hydrocarbon budgets. Highlights: C2 –C5 NMHC emission from straw-returned agricultural soil was studied. Straw-returning induces emissions of alkenes dominated by ethylene, propene and 1-butene. Microbes play an important role in C2 –C5 NMHC emission. Straw-returning is insignificance to C2 –C5 NMHC global budgets.